2-Phenylethanol in the leaves of Bursera velutina Bullock (Burseraceae) - Noge, Koji; Venable, D. Lawrence; Becerra, Judith X. (Instituto de Ecología, A.C., 2011)
The volatile composition of the leaves of Bursera velutina Bullock (Burseraceae) was determined by a gas chromatograph-mass spectrometer (GC–MS). The major component found was 2-phenylethanol (29.5%). This is the first report of 2-phenylethanol in the leaves of a species of the genus Bursera. In addition, B. velutina also produces monoterpenes, sesquiterpenes, diterpenes and alkanes, making it a species with one of the most complex chemical compositions in the genus. This diverse and unique blend of compounds may play an important role in plant defense against its herbivores.